Genomic analysis of Mycobacterium brumae sustains its nonpathogenic and immunogenic phenotype - Renau-Mínguez, Chantal; Herrero-Abadía, Paula; Ruiz-Rodriguez, Paula; Sentandreu, Vicente; Torrents, Eduard; Chiner-Oms, Álvaro; Torres-Puente, Manuela; Comas, Iñaki; Julián, Esther; Coscolla, Mireia (Frontiers in Microbiology, 2023)
M. brumae is a rapid-growing, non-pathogenic Mycobacterium species, originally isolated from environmental and human samples in Barcelona, Spain. M. brumae is not pathogenic and its in vitro phenotype and immunogenic properties have been well characterized. However, the knowledge of its underlying genetic composition is still incomplete. In this study, we first describe the 4 Mb genome of the M. brumae type strain ATCC 51384T assembling PacBio reads, and second, we assess the low intraspecies variability by comparing the type strain with Illumina reads from three additional strains. M. brumae genome is composed of a circular chromosome with a high GC content of 69.2 % and containing 3,791 CDSs, 97 pseudogenes, one prophage and no CRISPR loci. M. brumae has shown no pathogenic potential in in vivo experiments, and our genomic analysis confirms its phylogenetic position with other non-pathogenic and rapid growing mycobacteria. Accordingly, we determined the absence of virulence-related genes, such as ESX-1 locus and most PE/PPE genes, among others. Although the immunogenic potential of M. brumae was proved to be as high as Mycobacterium bovis BCG, the only mycobacteria licensed to treat cancer, the genomic content of M. tuberculosis T cell and B cell antigens in M. brumae genome is considerably lower than those antigens present in M. bovis BCG genome. Overall, this work provides relevant genomic data on one of the species of the mycobacterial genus with high therapeutic potential.